Unexpected heterogeneity and tissue-specific properties of the thymic hematopoietic antigen–presenting cell network - Yi Wang; Xin Liu; Amelie C. Bond; Seungyoul Oh; Sotaro Ochiai; Abbie R. Larson; Anita E. Qualls; Im Hong Sun; Michaël Chopin; James M. Gardner; Stephen L. Nutt; Franca Ronchese; et al. (Proceedings of the National Academy of Sciences, 2025)
Thymic hematopoietic antigen–presenting cells (hAPCs) play critical roles in regulating T cell development, but the identity, diversity, and transcriptional regulation of these cells are poorly understood. To address this, we characterized mouse thymic hAPCs in an unbiased manner utilizing physical interactions. Transcriptional profiling revealed the presence of CD8α + cDC1, SIRPα + cDC2, mature dendritic cells (DC), plasmacytoid DCs, macrophage, and B cell lineages in both mouse and human thymus. Notably, the composition and activation profile of DCs was altered in autoimmune mouse strains. Further, we found that the SIRPα + DCs are in fact a heterogeneous population consisting of DC3, transitional DCs, and true DC2s, all of which express a thymus-specific signature. Surprisingly, the differentiation of these thymic DC2s does not depend on IRF4. Finally, we described a thymic hematopoietic autoimmune regulator-expressing APC population resembling Janus cells that appear to express peripheral tissue antigens. Our findings thus reveal complexity of the thymic hAPC network.